Alteration in the pulsatility index values of the internal carotid and middle cerebral arteries after suspension of postmenopausal hormone replacement therapy: A randomized crossover study - PENOTTI, M; FARINA, M; CASTIGLIONI, E; GAFFURI, B; BARLETTA, L; GABRIELLI, L; VIGNALI, M (American journal of obstetrics and gynecology, 1996)
OBJECTIVE: The aim of the study was to investigate the effect of the suspension of hormone replacement therapy on blood flow in the internal carotid and the middle cerebral arteries. STUDY DESIGN: Doppler ultrasonography was used to measure the pulsatility index of the internal carotid and middle cerebral arteries of 23 women. The patients were all receiving continuous transdermal estradiol replacement therapy (50 μg/day) with a cyclic supplementation of medroxyprogesterone acetate every second month (10 mg/day for 12 days). The duration of the study was 12 months. The patients were randomly assigned to one of two groups. The first group (11 subjects) continued therapy for the first 6 months and then suspended it for the following 6 months; the second group (12 subjects) interrupted hormone replacement therapy for the first 6 months and then resumed it for the following 6 months. The internal carotid and middle cerebral artery pulsatility index was measured at the start of the 12-month period and then every 3 months. Serum estradiol levels were measured to check compliance. RESULTS: A statistically significant difference was found between the internal carotid and middle cerebral artery pulsatility index values of the two groups at each of the measurements after the first one. Over the first 6 months the pulsatility index values rapidly increased in the patients kept off hormone replacement therapy and remained stable in those receiving hormone replacement therapy. After the crossover at 6 months, the pulsatility index rapidly dropped to values similar to those at baseline in the patients who resumed hormone replacement therapy and increased in those who suspended therapy. CONCLUSIONS: Resistance to blood flow in cerebral vessels of postmenopausal women rapidly changes after hormone replacement therapy suspension. In postmenopausal women estrogen administration should be continued to maintain the favorable variations of vascular reactivity induced by hormone replacement therapy. (Am J Obstet Gynecol 1996;175:606-11.)